Determinan Ketepatan Pemberian Opini Audit Dengan Pengalaman Auditor Sebagai Variabel Moderasi - Christina, Christina; Ilyas, Meifida; Salsabila, Putri (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
This research aims to partially and simultaneously determine independence, ethics and competence on the accuracy of providing audit opinions, as well as the role of auditor experience as a moderator in this relationship. The research population is auditors registered at KAP South Jakarta. The research sample was 83 respondents. The sampling technique is purposive sampling. The analysis method is multiple linear regression. The partial research results show that ethics and competence influence the accuracy of providing an audit opinion, while independence does not influence the accuracy of providing an audit opinion. Furthermore, the auditor's experience which acts as a moderating variable is able to influence the relationship between ethics and competence, but weakens the relationship between independence and the accuracy of providing an audit opinion. Simultaneously the auditor's independence, ethics, competence and experience which act as moderating variables have an influence on the accuracy of providing an audit opinion